Implementation of Manila Bay Sustainable Development Masterplan (Mbsdm) and National Capital Integrated Coastal Development (Ncicd) Program in Mitigation Strategy of Sea Level Rise in Indonesia and Philippines - Najwa Belvana Balqis; Januari Pratama Nurratri Trisnaningtyas (Universitas Muhammadiyah Jember Press, 2024)
This research aims to compare the implementation of two policy projects in cooperation with the Dutch government to address sea level rise in two major cities. Focusing on two projects in the two Southeast Asian capitals of Manila and Jakarta with similar geographical locations, similar problems, and similar foreign cooperation partners, but have different implementations in the two countries. This research uses the theory of Comparative Policy to analyze the comparison of the effectiveness of program implementation in both countries. The method used in data collection is through secondary data, where the author does not directly collect data but through third parties in the form of previous articles and journals. Despite the fact that both projects cooperate with the Netherlands through the Netherlands International Water Ambitions (NIWA), they have different approaches. By involving the private sector in its funding, MBSDM concentrates more on nature-based solutions such as mangrove restoration and coastal ecosystem zoning. NCICD, on the other hand, concentrates on building large infrastructure intended to prevent tidal flooding quickly, such as the Giant Sea Wall, giant dykes and coastal reclamation.